Insensitivity in the pore size distribution of ultramicroporous carbon materials by CO2 adsorption. (30th October 2020) - Cornette, V.; Villarroel-Rocha, J.; Sapag, K.; Delgado Mons, R.; Toso, J.P.; López, R.H.
Abstract: Accurate quantification of ultramicropores is critical to optimizing and understanding the performance of carbon materials in many applications. The pore size distributions (PSD) were calculated from the CO2 adsorption isotherms by Non-local Density Functional Theory (NLDFT) and Grand Canonical Monte Carlo simulations (GCMC). The PSDs obtained using a pseudo-spherical potential for CO2 interaction have the same qualitative behavior, reporting several peaks in the ultramicroporous region. These results contradict the hypothesis that highly disordered microporous carbon materials have a widely distributed PSD without sharp spikes. In this work, we investigate the insensitivity in the characterization of different microporous materials and the origin of the artificial gaps that arise in models with pseudo-spherical potential (NLDFT and GCMC). Furthermore, we study the characterization of these materials using Monte Carlo simulations, which incorporate the multi-site model potential achieving improved PSDs. Graphical abstract: Image 1 Highlights: The accurate characterization of different carbon materials in the ultramicropores range was studied. The insensitivity in the characterization of carbonaceous microporous adsorbents, from CO2 adsorption isotherms, was detected. The influence of the regularization parameter (λ) in the prediction of PSD (CO2 ), using NLDFT and GCMC was explored. The sensibility in the PSD's prediction using the GCMC and the multi-site potential for the adsorbate interaction was studied. The multi-site potential interaction produces a more reliable characterization of this kind of material.